PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASILBELAJAR SISWA DALAM PEMBELAJARAN IPS TENTANG SUMBER DAYA ALAM: Penelitian Tindakan Kelas Iv Pada Materi Pembelajaran Tentang Sumber Daya Alam Pembelajaran Ips Di Sd Negeri Mekarlaksana Kecamatan Cilaku Kabupaten Cianjur - Idho Suryawan, - (2012)
This research in based on the low of pupil's result in their study. One of the cause, is the pupil never been active in their study, that's why the new model is must be make to increase the achievement of the pupil and to increase the teacher's creativity. Contextual teaching and learning is a formula to solve those problems. In that case we can formulate what's kind of step, what kind of activity and the pupil result using of Contextual teaching and learning formula in social subject.and The purpose of this research is to know the increase of pupil's result after using that's new formula. Contextual teaching and learning formula is influenced by constructivism philosophy, who thing that science is not a gift by someone else such a teacher, but science is a result of a experience construction. that's why this new formula is concern to the involvement of a pupil to find a subject. That's mean learning process is oriented by a direct experience. This research is a research of the class (PTK) adapted with Kemmis and Mc. Taggart model with three cycles. And the subject is 29 pupils of forth year class at SDN MekarlaksanaCilakuCianjur. During this research the cyclesare increase, such a creativity of a teacher, learning activities and the final result of pupil's study. In the first cycle the rate of individual result is about 6,68 and the grup's result is about 6,91. In the second cycle the rate of individual result is about 7,13 and the grup's result is 7,6. And in the third cycle the rate of individual result is about 7,86 and the grup's result is about 8,4. From those results it can be concluded that Contextual teaching and learning formula it's successfully increase pupil's achievement in the social science with a natural resources as it's subject. That's why I suggest Contextual teaching and learning formula it's using in the learning process in social science.